Core curriculum for vascular nursing - Christensen, Cynthia Rebik; Lewis, Patricia A. (Wolters Kluwer Health ; Society for Vascular Nursing, 2014)
The official publication of the Society for Vascular Nursing, the newly updatedCore Curriculum for Vascular Nursingprovides core vascular nursing information essential to new and experienced practitioners alike. Presented in a quick-reference outline, the evidence-based content addresses a wide range of vascular conditions, as well as diagnostics, vascular anatomy, surgical interventions, medications, and patient education. Whether you are prepping for the certification exam, involved in continuing education, or treating a challenging patient condition, this is an unbeatable resource. New content on new technology and recent advances in vascular nursing. New content on ischemic nephropathy. Read-at-a-glance outline format, illustrated with numerous tables and charts. Coverage of topics including: the evolution of vascular nursing; vascular assessment and diagnosis; vascular nursing research; recommendations for treatment of carotid artery stenosis, aortic aneurysm, renal artery stenosis, vascular access, venous disease, vascular trauma, amputations, and lymphedema. Can serve as a manual for nursing instructors, and as a foundation for vascular nursing training and courses.
Preceded by: Core curriculum for vascular nursing / Patricia A. Lewis, editor. ©2007.
Keywords: Cardiovascular system -- Diseases -- Nursing -- Outlines, syllabi, etc.; Cardiovascular Nursing -- methods; Vascular Diseases -- nursing; Appareil cardiovasculaire -- Maladies -- Soins infirmiers -- Résumés, programmes, etc.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Clinical Medicine.; MEDICAL -- Diseases.; MEDICAL -- Evidence-Based Medicine.; MEDICAL -- Internal Medicine.; Cardiovascular system -- Diseases -- Nursing; Outline; Outlines and syllabi